All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 168745 by MikeH last updated on 17/Apr/22
∫1x+x−1dx=??
Commented by safojontoshtemirov last updated on 17/Apr/22
∫dxx+x−1=x−1=t;x=t2+1;dx=2tdt∫2tdtt2+t+1=∫2t+1t2+t+1dt−∫1t2+t+1dt=I1−I2I1=∫d(t2+t+1)t2+t+1dt=ln(t2+t+1)+C1=ln(x−1+x−1+1)+C1I2=∫1t2+t+1dt=∫1(t+12)2+34dt=43∫1(t+1232)2+1dt=43∫1(2t+13)2+1dt=43⋅32∫d(2t+13)(2t+13)2+1=13arctg(2t+13)+C2=23arctg2x−1+13+C2I1−I2=ln(x−1+x−1+1)−23arctg2x−1+13+C
Answered by blackmamba last updated on 17/Apr/22
=∫x−x−1x2−x+1dx=∫12(2x−1)+12x2−x+1dx−∫x−1x2−x+1dx=12ln(x2−x+1)+12∫dx(x−12)2+(32)2−∫x−1x2−x+1dx
Terms of Service
Privacy Policy
Contact: info@tinkutara.com